Multi-trap energy states in GaN HEMTs : characterization and modeling - Binit Syamal (2020)
In this work, presence of multi-trap energy (MTE) levels in the GaN energy bandgap of AlGaN/GaN HEMT is studied based on conductance method as well as temperature-dependent current transient measurements. Using conductance method, it is observed that the MTE model shows a better fit with the measurement data as compared to the single-trap energy (STE) model. Temperature-dependent current transient analysis under fully ON-state stress conditions has also confirmed the presence of distribution of trap energy states in the GaN energy bandgap. The DC trap model is extended to capture the effect of MTE levels. For STE level, the emission-time constant factor saturates very quickly with increasing drain voltage. However, with MTE levels, the time-constant factor continues to increase and saturates at higher drain bias, exhibiting a similar trend as observed in current transient analysis under ON-state stress measurements. The DC trap model with MTE level fit nicely with the numerical simulation data, thus, justifying the physics-based model.